Edukasi Pencegahan Obesitas Dan Diabetes Melalui Pola Hidup Sehat Di Masyarakat - Ismail Ismail; Muhammad Basri; Sukriyadi Adi; Sitti Rahmatia; Muhammad Nur (Jurnal Inovasi Pengabdian Masyarakat Celebes, 2025)
Background: Non-communicable diseases (NCDs) such as diabetes, hypertension, and cardiovascular disease are the leading causes of death in Indonesia. Inactive lifestyles and low awareness of physical fitness are major risk factors that can be prevented through early detection. Objective: This community service program aims to assess the physical fitness of employees of the Nursing Department of the Makassar Ministry of Health Polytechnic as a strategy for preventing NCDs. Implementation Method: The methods used include anthropometric measurements (height, weight, Body Mass Index/BMI, and waist circumference), metabolic parameters (fasting blood sugar and cholesterol levels), and cardiovascular fitness assessment (blood pressure). Results: A total of 42 participants aged 30–65 years participated in this activity. The results showed that 61.9% of participants were obese, 47.6% had high blood sugar levels, and 26.2% had high cholesterol levels. These findings indicate that the majority of participants are at high risk for NCDs. Conclusion: This program successfully increased participants' awareness of the importance of physical fitness and early detection of NCD risk factors. Routine implementation of fitness screening in the workplace can be a strategic step in preventing and controlling NCDs and improving the quality of life for healthcare workers. Abstracts should conclude with a commentary on the significance of the results or a brief conclusion.